Edukasi Pencegahan Cidera Bahu Terhadap Atlet Rugby di PRUI Boyolali - Wahyu Tri Sudaryanto; Ilham Nur Hihmawan; Ajeng Sabtorini; Ike Puteri Elgina (Universitas 45 Surabaya, 2023)
Exercise is a form of planned and structured physical activity that involves repetitive body movements and is aimed at improving physical fitness. Seeing the game of rugby sport is vulnerable to injury if it is not paid attention to the correct warm-up. Rugby poses a high risk of injury. This activity will be held on June 10, 2023 in the field of Winong Hamlet, Boyolali District, Boyolaali Boyolali Regency, Central Java using leaflet media and direct practical explanations. The result obtained from this rugby community activity is that athletes can add insight into the knowledge of handling acute injuries to the shoulder using the PEACE method which is proven by the results of the evaluation value carried out. The conclusion is that the use of poster media and direct practical explanations has a very good impact in increasing the knowledge of rugby athletes about handling acute injuries.